Effect of temperature and bulking agents on deep bio-drying of high-solid anaerobically digested sludge. Issue 14 (1st October 2020) - Liu, Zhanguang; Tan, Xuejun; Wang, Yixian; Zou, Weiguo; Zhang, Chen
Abstract: The effect of temperature and bulking agents, namely sawdust (SD), wheat bran (WB), and wheat straw (WS), on bio-drying of high-solid anaerobically digested sludge (ADS) was evaluated. A mixture of dewatered ADS with municipal sludge compost product (CP) and different bulking agents was loaded into a 180-L pilot-scale reactor. Intermittent aeration of 12 L min −1 with 20 min run/40 min stop was adopted during the whole bio-drying process. After 18 to 21 days of bio-drying, volatile solids (VS) in the trials with SD, WB, and WS degraded at a rate of 86.6, 284.3, and 344.2 g kg −1 initial VS, respectively. The matrix with easier biodegradable WB and WS achieved faster and higher water removal at a rate of 692.7 to 764.2 g kg −1 initial water, and a higher temperature cumulation of 373 to 427 °C·d. Approximately 70% of the bio-generated heat consumed for water evaporation. In the trials with WB and WS, the matrix moisture content decreased to below 39%, and the weight declined by above 48%. Water removal and VS degradation contributed to 85.2 ± 3.4% and 14.8 ± 3.4% of the total weight loss, respectively. The residual WB in bio-dried products (BP) caused low germination index (GI), indicating possible phytotoxic effects in soils. WS was determined to be the best agent with significantly higher GI and lower cost compared to WB, implying promising land utilization potential of BP.